Jewish amulets, magic bowls, and manuals in Aramaic and Hebrew - Bohak, Gideon (Guide to the study of ancient magic, 2019)
This chapter focuses on Jewish Aramaic and Hebrew ritual materials from Late Antiquity to the early medieval period including: Palestinian amulets and spells, Babylonian magic bowls, and the recipes preserved in the Cairo Genizah. Materials are interrogated for evidence of social context (gender of clientele) and the status of these kinds of materials in Judaism at the time of composition. Finally, it compares Jewish materials to non-Jewish analogues.